Distinct Habitats Select Particular Bacterial Communities in Mangrove Sediments - Lidianne L. Rocha; Geórgia B. Colares; Vanessa L. R. Nogueira; Fernanda A. Paes; Vânia M. M. Melo (International Journal of Microbiology)
We investigated the relationship among environmental variables, composition, and structure of bacterial communities in different habitats in a mangrove located nearby to an oil exploitation area, aiming to retrieve the natural pattern of bacterial communities in this ecosystem. The T-RFLP analysis showed a high diversity of bacterial populations and an increase in the bacterial richness from habitats closer to the sea and without vegetation (S1) to habitats covered by Avicennia schaueriana (S2) and Rhizophora mangle (S3). Environmental variables in S1 and S2 were more similar than in S3; however, when comparing the bacterial compositions, S2 and S3 shared more OTUs between them, suggesting that the presence of vegetation is an important factor in shaping these bacterial communities. In silico analyses of the fragments revealed a high diversity of the class Gammaproteobacteria in the 3 sites, although in general they presented quite different bacterial composition, which is probably shaped by the specificities of each habitat. This study shows that microhabitats inside of a mangrove ecosystem harbor diverse and distinct microbiota, reinforcing the need to conserve these ecosystems as a whole.